Effects of varying levels of sodium chloride on chemical composition of cage layer droppings (2010)
Animal Scientists, through extensive research works have made tremendous achievements on reclaiming the nutrients contained in poultry waste by using it as feed ingredient for different classes of animals thereby reducing feed cost. Despite the many ways of its utility, the slurry nature of poultry droppings, most often complicates its handling and renders it totally useless. Four graded levels of dietary sodium chloride (0.30%, 0.45%, 0.60%, 0.75%) in an iso-nitrogenous and iso-caloric diets were fed to two strains of laying domestic chicken. The moisture content of the dropping increased insignificantly (P< 0.05) with increased dietary salt. While dry matter content of the droppings decreased insignificantly (P< 0.05) with increased dietary salt content. Results indicate that increasing dietary salt at the above levels in cage layers increases moisture level of poultry droppings insignificantly (P< 0.05) making it to be more slurry.